2005
DOI: 10.1126/science.1107981
|View full text |Cite
|
Sign up to set email alerts
|

Cassini Imaging Science: Initial Results on Phoebe and Iapetus

Abstract: The Cassini Imaging Science Subsystem acquired high-resolution imaging data on the outer Saturnian moon, Phoebe, during Cassini's close flyby on 11 June 2004 and on Iapetus during a flyby on 31 December 2004. Phoebe has a heavily cratered and ancient surface, shows evidence of ice near the surface, has distinct layering of different materials, and has a mean density that is indicative of an ice-rock mixture. Iapetus's dark leading side (Cassini Regio) is ancient, heavily cratered terrain bisected by an equator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
148
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(156 citation statements)
references
References 20 publications
7
148
0
1
Order By: Relevance
“…Spectroscopic studies show a large diversity of colors (ranging from gray to very red ) among observed irregular satellites of four outer planets (Cruikshank 1980;Degewij et al 1980;Dumas et al 1998;Brown 2000;Sykes et al 2000;Grav et al 2003Porco et al 2005). This diversity would be difficult to understand if irregular satellites were captured from a local and dynamically cold population of planetesimals at the planet's heliocentric position, because in such a case the colors should be homogeneous (reflecting the local composition) and there should exist a clear color gradient of irregular satellites with heliocentric distance (i.e., from Jupiter to Neptune).…”
Section: Introductionmentioning
confidence: 99%
“…Spectroscopic studies show a large diversity of colors (ranging from gray to very red ) among observed irregular satellites of four outer planets (Cruikshank 1980;Degewij et al 1980;Dumas et al 1998;Brown 2000;Sykes et al 2000;Grav et al 2003Porco et al 2005). This diversity would be difficult to understand if irregular satellites were captured from a local and dynamically cold population of planetesimals at the planet's heliocentric position, because in such a case the colors should be homogeneous (reflecting the local composition) and there should exist a clear color gradient of irregular satellites with heliocentric distance (i.e., from Jupiter to Neptune).…”
Section: Introductionmentioning
confidence: 99%
“…Cassini discovered that dark material, probably from Phoebe which orbits at 215 Saturn radii, is deposited onto the surface and is then "thermally segregated" -it warms in sunlight, is mobilized and then re deposited on colder areas (Tosi et al 2010). Iapetus also has an equatorial ridge rising 10 km, with peaks up to 20 km, above the moon's surface (Porco et al 2005), possibly from earlier rapid rotation or aggregation from a collapsed ring. Phoebe as a source is made more likely by the discovery using Spitzer Space Telescope data of a disc of material extending between at least 128 and 207 Saturn radii, associated with Phoebe (Verbiscer et al 2009).…”
Section: Icy Satellitesmentioning
confidence: 99%
“…Himalia and Phoebe by Cassini (Porco et al 2003(Porco et al , 2005, or Nereid by Voyager-2 (Thomas et al 1991). Recently, thermal emission data obtained with the MIPS camera of the Spitzer Space Telescope (Rieke et al 2004) and the PACS camera of the Herschel Space Observatory (Poglitsch et al 2010) also provided independent size and albedo estimates for Sycorax (Lellouch et al 2013) and Nereid ).…”
Section: Introductionmentioning
confidence: 99%